Emerging Freshwater Pollutants: Analysis, Fate and Regulations - Dalu, Tatenda; Tavengwa, Nikita (Elsevier, 2022)
Emerging Freshwater Pollutants: Analysis, Fate and Regulations comprises of 20 chapters, all written by leading experts.This book is written in the most practical terms and is easy to understand, with numerous helpful examples and case studies and can be used as a practical guide and important educational tool on issues concerning freshwater.